Effects of Variations in Pedagogical Feedback in English Learning (2019)
This research arises from the interest on teaching work inside and outside the class- room, looking for change, flexibility and transformation of realities. Its general objective is to determine the differential effect of variations in feedback parameters for success and error in basic skills learning of English subject in eight grade students of a municipal educational institution in the Colombian southwest. It was developed under the quantitative paradigm, of explanatory type and factorial design with three independent variables: latency, specificity and feedback valence. A pilot test was conducted, which allowed strengthening of the mani- pulation strategy of independent variables and the instruments application. The reliability of the instruments used was estimated using Cronbach ́s Alpha for English pre-test and post-test, which yielded indexes of 0.77 and 0.76 respectively. The specificity component interacts with latency, so that the specific and short feedback condition is the combination of components that generate the highest learning skills. Moreover, the short feedback kept the motivation for the task constantly throughout the different instances of learning assessment